On the stabilization of the energy of a harmonic oscillator disturbed by random processes of the white and shot noises types. (2000) - Kulinich, Grigori L.; Kushnirenko, Svitlana V.
Abstract : In this paper the behavior of the instantaneous energy of a harmonic oscillator is investigated in the case when at a certain angle to the vector of the phase velocity of the oscillator, random disturbances of the white and shot noises types are acting.